2007
DOI: 10.1111/j.1365-2958.2007.05840.x
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol, a common sesquiterpene, inhibits PQS production in Pseudomonas aeruginosa

Abstract: SummaryFarnesol is a sesquiterpene produced by many organisms, including the fungus Candida albicans. Here, we report that the addition of farnesol to cultures of Pseudomonas aeruginosa, an opportunistic human bacterial pathogen, leads to decreased production of the Pseudomonas quinolone signal (PQS) and the PQS-controlled virulence factor, pyocyanin. Within 15 min of farnesol addition, decreased transcript levels of pqsA, the first gene in the PQS biosynthetic operon, were observed. Transcript levels of pqsR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
263
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(268 citation statements)
references
References 58 publications
3
263
0
2
Order By: Relevance
“…Farnesol (Table 3) is a signaling molecule produced by Candida albicans, an opportunistic fungal pathogen often found in mixed infections with P. aeruginosa in clinical settings. Farnesol-mediated inhibition of PQS production and PQS-controlled pyocyanin production was concentration dependent and was due to decreased expression of the pqs operon, which the authors propose to result from the farnseol-mediated formation of nonproductive interactions of the transcriptional regulator PqsR with the pqsA promoter (124). In addition, it was shown that naturally occurring levels of farnesol produced by C. albicans were sufficient to suppress PQS production during coculture, suggesting a physiologically relevant role for farnesol in modulation of PQS signaling.…”
Section: Inhibition Of Pqs Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farnesol (Table 3) is a signaling molecule produced by Candida albicans, an opportunistic fungal pathogen often found in mixed infections with P. aeruginosa in clinical settings. Farnesol-mediated inhibition of PQS production and PQS-controlled pyocyanin production was concentration dependent and was due to decreased expression of the pqs operon, which the authors propose to result from the farnseol-mediated formation of nonproductive interactions of the transcriptional regulator PqsR with the pqsA promoter (124). In addition, it was shown that naturally occurring levels of farnesol produced by C. albicans were sufficient to suppress PQS production during coculture, suggesting a physiologically relevant role for farnesol in modulation of PQS signaling.…”
Section: Inhibition Of Pqs Productionmentioning
confidence: 99%
“…In addition, it was shown that naturally occurring levels of farnesol produced by C. albicans were sufficient to suppress PQS production during coculture, suggesting a physiologically relevant role for farnesol in modulation of PQS signaling. Interestingly, other compounds containing the long-chain isoprenoid backbone were also able to repress PQS production, although to differing degrees, potentially providing a novel scaffold for the design of PQS synthesis inhibitors (124).…”
Section: Inhibition Of Pqs Productionmentioning
confidence: 99%
“…and a few animal pathogens, indicating that LuxS at large would have a metabolic role in other bacteria (Rezzonico and Duffy, 2008). Scientists are now also beginning to address the prospect of interspecies and interkingdom signaling using various signaling molecules among distantly related organisms which colonize similar niches (Cugini et al, 2007;. This signaling can lead to cooperation as well as competition/ inhibition.…”
Section: Ahls and Bacterial Interspecies Signalingmentioning
confidence: 99%
“…Interestingly, in vitro studies have demonstrated that these signaling interactions between P. aeruginosa and C. albicans may in fact be bidirectional. It has been observed that the addition of farnesol leads to decreased Pseudomonas quinolone signal (PQS) production in P. aeruginosa and reduced levels of the PQS-regulated virulence factor pyocyanin (Cugini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%